The unconventional geminivirus Beet curly top Iran virus: satisfying Koch's postulates and determining vector and host range. (6th December 2012) - Soleimani, R.; Matic, S.; Taheri, H.; Behjatnia, S. A. A.; Vecchiati, M.; Izadpanah, K.; Accotto, G. P.
Abstract Beet curly top Iran virus (BCTIRV) is a geminivirus with unusual genomic organisation, recently reported in Iran, infecting sugarbeet and a few other plant species. Although three BCTIRV sequences have been reported, demonstration that BCTIRV DNA is the causal agent of the disease was missing. A full‐length genomic DNA was obtained from symptomatic leaves of sugarbeet collected in the Sivand area of Iran, and its nucleotide sequence was determined (BCTIRV‐Siv, 2845 nt). To satisfy Koch's postulates, an infectivity assay was developed by inserting a 1.4‐mer of BCTIRV‐Siv DNA in Agrobacterium tumefaciens and using it in agroinoculation experiments. The cloned viral DNA was capable of infecting sugarbeets, reproducing the leaf curling and vein enations observed in the field. These results demonstrate that the single DNA component of BCTIRV is sufficient for infectivity. Host range studies indicated that some economically important crops can be affected, such as spinach, tomato and sweet pepper, as well as important laboratory plants including Nicotiana benthamiana, Arabidopsis thaliana and Jimson weed. Circulifer haematoceps, the dominant leafhopper species present in sugarbeet fields in Iran, was successfully used to transmit the disease. The availability of an infectious clone will facilitate extended host range studies, to determine the potential risks to other crops, as well as genetic studies on this unusual member of the family Geminiviridae.